Study on simulation of cement plug—formation interface stripping failure and main influencing factors - Wang, Jiangshuai; Cai, Chuchu; Fu, Pan; Deng, Song; Tang, Zheng (Frontiers in Earth Science, 2023)
Among the existing gas storage facilities, salt cavern gas storage has the advantages of high injection production efficiency, low gas cushion volume, safety, flexibility, etc. It is of great significance to speed up the construction of underground gas storage by transforming abandoned salt caverns of salt industry into underground gas storage. However, old salt cavern wells cannot be directly converted into gas storage injection and production wells, so the old wellbore must be plugged to ensure the effectiveness of plugging. Therefore, a set of plugging optimization technology for salt cavern gas storage wells is urgently needed. In this paper, a 3D finite element model of the cement plug-formation system based on cohesive element method is established for the milling and plugging of the old well in the salt cavern gas storage section. The results show that under the condition of constant gas storage pressure, a certain degree of small deformation will occur at the bottom of the cement plug after compression, resulting in the shear direction deformation of the cement plug formation cementation interface, and peeling will occur after accumulation to a certain extent. With the increase of simulation time, the length of stripping section gradually increases and tends to be stable, and reaches the limit of stripping failure length. In the process of research, the factors and laws affecting the stripping failure length were also analyzed. It was found that the stripping failure length of cement plug formation cementation interface was related to the maximum operating pressure of gas storage, cement plug length, cement plug diameter, elastic modulus, Poisson’s ratio and other factors. The research results are helpful to judge whether the milling and plugging length of the old well section is sufficient, and provide theoretical guidance for ensuring the long-term safe operation of the gas storage.